x-3=4/5(9-9x)

Simple and best practice solution for x-3=4/5(9-9x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-3=4/5(9-9x) equation:


x in (-oo:+oo)

x-3 = (4/5)*(9-(9*x)) // - (4/5)*(9-(9*x))

x-((4/5)*(9-(9*x)))-3 = 0

(-4/5)*(9-9*x)+x-3 = 0

x-4/5*(9-9*x)-3 = 0

x-4/5*(9-9*x)-3 = 0

41/5*x-36/5-3 = 0

41/5*x-51/5 = 0

41/5*x-51/5 = 0

41/5*x-51/5 = 0 // + 51/5

41/5*x = 51/5 // : 41/5

x = 51/5/41/5

x = 51/41

x = 51/41

See similar equations:

| 2x/11(7-2)=7x+10 | | .7+.5(x+2)=.3x-1 | | 7x-x=12+2x | | 10x-12=-4x+2 | | (6w-7)/5 | | 9-7a+5a=11 | | 5x+3=-2x+5 | | (x-5)(x-5)=10 | | x/5+15=7-4x+8 | | 18x-y=424 | | 20*1/5 | | 15/2=x/2+3/2 | | 7,1/2=x+3/2 | | 71/2=x+3/2 | | 3u/2=-21 | | 7u/3=14 | | -x+3(x-4)=12x-1 | | 7/2*5/2 | | 16/3*19/2 | | 2x+34=3x+34 | | 2p-3p=5(p+6) | | 2p-3p=(p+6) | | 3-2x=12(1/3x-9/4) | | y-130=-23/4(x-0) | | x/4+5/12=3x/4-1/6 | | 2=13x | | 2(-x-5)=-3x-7 | | [3x+4]=12 | | 4-2d=-2(2d-4) | | .2x-.3=-.7x-2.1 | | 70x-x^2+105=0 | | -13-9x=21-16x |

Equations solver categories